Linchamento virtual : discursos de ódio aos profissionais da educação em Mato Grosso - Petini, Luiz Fernando (2023)
This dissertation aimed to analyze the reasons and situations in which social networks are used to promote virtual lynching against education professionals in the state of Mato Grosso. To do so, we sought to understand how virtual environments are being used for this virtual persecution in the context of Zygmunt Bauman's liquid modernity. The research used an inductive and comprehensive method, structured in two phases, one exploratory and one descriptive. In the first stage, a bibliographic search was conducted to review articles and periodicals available in open sources. In addition, newspapers and news sites published on the subject were analyzed. In the second phase, a questionnaire was made available to educators in the state of Mato Grosso to know the experience and opinions of these professionals about virtual lynching. In the descriptive phase, the results obtained were presented. It was found that although lynching is not a recent phenomenon, the virtual environment has amplified these actions, especially in the face of the vulnerability and fragility of social relations in liquid modernity. Furthermore, despite limitations due to ethical issues, it was possible to conclude that virtual lynching occurs when fake news and hate speech are disseminated against educators. Likewise, the initially established hypothesis that virtual lynching is more recurrent during strikes and elections was confirmed. Moreover, this phenomenon poses dangers that go beyond the virtual environment, harming the victim in psychological, material and social aspects. Virtual lynching is still a challenge in our society, particularly due to the absence of legal norms to prevent such actions. Therefore, it is necessary to institute public policies and legislative changes aimed at combating this virtual persecution, especially against educators.